Evaluation of Coretax Implementation Using A Modified Delone & Mclean Model Based on Indonesian Taxpayers Perspective - Chumairo, Afiifatul; Mohammad Khoiru Rusydi; Noval Adib (Universitas Muhammadiyah Surakarta, 2026)
This study evaluates Indonesia’s Coretax implementation from taxpayers’ perspectives using a modified DeLone and McLean IS Success Model integrating trust in government and government support. A quantitative online survey of 184 individual and corporate taxpayers was analyzed using PLS-SEM to assess measurement validity and mediation effects. The results show that system quality, service quality, and government support significantly increase net benefits through user satisfaction. However, information quality and trust in government do not significantly affect net benefits via satisfaction. These findings highlight the importance of system stability, responsive support, and sustained government facilitation to maximize implementation benefits.